Inventory - Andrew Leach (Footprint)
What is the value, now, in conducting historical research into architectural ideas? The paper addresses the function of contemporary PhD research in light of a) the so-called historiographical turn in architectural history, theory and criticism research consolidated in the last decade or so; b) the broader positions in which critical and historical knowledge and practices are implicated within present-day architectural culture; and c) the particular circumstances of PhD research in architecture in Australian universities.